PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN - Anggriani Atika; Yuntawati Fristin; Agung Suwandaru (Jurnal Bisnis dan Manajemen, 2017)
The aim of research to identify and analyze the influence of transformational leadership on employee performance and analyze the effect of communication on employee performance, identify and analyze the effect of transformational leadership and communication simultaneously on employee performance. This type of research is survey with quantitative approach. The population in this study were all employees of PT PLN Rayon Malang as many as 72 people. The sampling technique used in this study is saturated or census sampling technique, namely the determination of the number of samples from all members of the population that is 72 people. The analytical tool used is multiple linear regression analysis.The study concluded that: 1. (X1) Transformational leadership has a significant positive effect (Y) employee performance. 2. (X2) Communications has a significant positive effect (Y) 3. Simultaneously employee performance (together) (X1) and transformational leadership (X2) Communications significant effect on (Y) employee performance. 4. Given the magnitude of the effect (X1) and transformational leadership (X2) Communication to the (Y) employee's performance of 55.3% while the remaining 44.7% is influenced by other factors. Other factors, one of which is the ability to affect the performance of employees. 5. (X1) Transformational leadership has a dominant influence on employee performance than communication DOI : https://doi.org/10.26905/jbm.v4i1.1709